Electromiographic analysis of femoral quadríceps in futsal and volleyball amateur athletes - Flavia Angela Servat Martins; Aline Bevervanzo dos Santos; Luiz Augusto da Silva; Julio Cesar Lacerda Martins (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2020)
This research has as its subject the electromyographic analysis of the femoral quadriceps in futsal and volleyball amateur athletes. It is noteworthy that the sample in this direct and quantitative field study was characterized primarily by age, body mass, stature and electromyographic evaluations of the muscles that form (or make up) the quadriceps. The objective of this study was to evaluate the relation between quadriceps femoral contraction between amateur futsal and volleyball players. The subjects of the survey were 12 amateur futsal athletes and 12 amateur volleyball athletes. A comparative analysis of quadriceps femoral contraction between futsal and volleyball athletes was developed. The inferential statist analysis to compare the studied variables with the use of the "t-test" for independent samples allows to compare independent groups whose scales were measured on a numerical scale. The results showed differences in the left rectus femoris muscles and left and right sides, among the hypotheses raised for this difference are the muscles required in each sport, the period of the training macrocycle in which the athletes are found, the frequency in strength training, or most likely all these allied associated.